Using of workbook on the subject «Physics and astronomy» in English at the secondary school - Shaimerdenova, K.M.; Tussypbayeva, A.S. (KSU Publ., 2018)
The article considers a multilingual education which is a new program of Kazakhstan’s education system. This education program carries out not only the teaching of languages (Kazakh, Russian and English languages) but also the teaching of disciplines of natural sciences in the languages mentioned above. Base on the example of physics the article presents some principles and approaches of teaching natural science disciplines in English by using workbook of «Physics and astronomy». It helps to teacher to make a correct procedure of a lesson and organize students’ activity for effective mastering both physics material and language skills. The main didactic purpose of the workbook is to speed up process of mastering the teaching material, i.e. to bring the educational process closer to the most effective characteristics. One of the main advantages of the workbook is that it allows teacher to control flow and formation of students` thinking activity. The workbook will help to formulate necessary knowledge, skills and skills for students. Thanks to the workbook on the subject «physics and astronomy», the lesson material is better understood, the lesson time is rationally used. The effectiveness of teaching Physics through a foreign language is opened by numerous advantages, such as formation of intercultural knowledge and understanding; development of intercultural skills; introduction of a broader cultural context; expansion of school and university profile; increase of general and specific language competence; development of communication skills; preparation for future research and / or labour activity; addition of individual learning strategies; increase of students` motivation.
Орта мектепте оқытуда ағылшын тілінде «Физика жəне астрономия» пəні бойынша жұмыс дəптерін қолдану
Использование рабочей тетради по предмету «Физика и астрономия» на английском языке в средней школе
Keywords: workbook; physics and astronomy; tasks; multilingual education; school; science direction; language skills